Molecular mechanism of modified Huanglian Wendan decoction in the treatment of polycystic ovary syndrome. Issue 15 (14th April 2023) - Wu, Zhaojing; Yang, Tiantian; Ma, Hongbo
Abstract : To investigate the mechanism of modified Huanglian Wendan decoction in the intervention of polycystic ovary syndrome (PCOS) by network pharmacology and molecular docking. The ingredients and targets of modified Huanglian Wendan decoction were retrieved from the traditional Chinese medicine Systems Pharmacology database. Related targets of PCOS were screened by Comparative Toxicogenomics Database database. Cytoscape 3.7.2 (https://cytoscape.org/ ) was used to draw the target network diagram of "traditional Chinese medicine - ingredient - PCOS, " STRING database was used to construct the target protein interaction network. NCA tool of Cystoscape 3.7.2 was used to carried out topology analysis on PPI network, core components and key targets were obtained. Gene ontology and Kyoto encyclopedia of genes and genomes enrichment analysis were carried out for the intersection targets by David database. AutoDockTools 1.5.6 software (https://autodock.scripps.edu/ ) was used to conduct molecular docking verification of key components and key targets. Ninety-one ingredients of the modified Huanglian Wendan decoction and 23, 075 diseases targets were obtained, 155 Intersection targets of the drug and disease were obtained by R language, Veen plot was drawn. Gene ontology enrichment analysis obtained 432 biological processes, 67 cell components, 106 molecular functions. Fifty-four Kyoto encyclopedia of genes and genomes enrichment pathways ( P < .05) including tumor necrosis factor, hypoxia-induced factors-1, calcium, and drug metabolism-cytochrome P450 signaling pathway. Molecular docking showed quercetin, luteolin, kaempferol, and baicalein were stable in docking with core targets. Network pharmacology and molecular docking were used to preliminarily study the mechanism of action of modified Huanglian Wendan decoction in the treatment of PCOS, which laid foundation for future experimental research and clinical application.